Challenges and solutions for the implementation of computer-based test learning evaluation at SMKN 2 Bandung - Azzahra Putri Imanda; Dea Apriliyani; Dewi Allyya Suci Putri Anjani (Universitas Pendidikan Indonesia, 2024)
This article explores the implementation of Computer-Based Testing (CBT) as a summative assessment method at SMK Negeri 2 Bandung, aiming for success and sustained benefits in the Indonesian education system. CBT includes diverse question formats, from multiple-choice to interactive simulations. The research objectives are: (1) describing CBT planning as a learning evaluation, (2) explaining CBT execution to enhance students' honesty in final exams at SMKN 2 Bandung, and (3) analyzing CBT results as a learning evaluation of students' honesty. This study delves into dimensions, context, and meanings related to the research subject using a qualitative approach with a descriptive method through interviews and surveys. Descriptive methods outline emerging characteristics and behaviors in the research context. This research enriches understanding of Information and Communication Technology's (ICT) role in educational transformation and proposes effective learning evaluation measures leveraging technology. The integration of CBT reflects a progressive step toward advancing education assessment methodologies. Abstrak Artikel ini membahas penerapan Computer-Based Testing (CBT) sebagai metode penilaian sumatif di SMK Negeri 2 Bandung, dengan harapan keberhasilan dan manfaat berkelanjutan bagi sistem pendidikan Indonesia. CBT mencakup variasi pertanyaan, mulai dari pilihan ganda hingga simulasi interaktif. Tujuan penelitian ini adalah mendeskripsikan perencanaan dan pelaksanaan CBT untuk meningkatkan kejujuran peserta didik dalam ujian akhir semester di SMKN 2 Bandung, serta menganalisis hasil CBT sebagai evaluasi pembelajaran terhadap kejujuran peserta didik. Penelitian ini menggunakan pendekatan kualitatif dan metode deskriptif dengan wawancara dan survei. Pendekatan ini dipilih untuk mengeksplorasi dimensi, konteks, dan makna terkait subjek penelitian. Metode deskriptif digunakan untuk menguraikan karakteristik dan perilaku dalam konteks penelitian. Pentingnya penelitian ini terletak pada kontribusinya terhadap pemahaman peran Teknologi Informasi dan Komunikasi (TIK) dalam transformasi pendidikan, serta usulan langkah-langkah evaluasi pembelajaran yang efektif melalui teknologi. Integritas CBT mencerminkan langkah progresif menuju pengembangan metodologi penilaian pendidikan. Kata Kunci: Evaluasi; penilaian sumatif; tes berbasis komputer